RELATIONSHIP BETWEEN SALT SENSITIVITY AND MORPHO-FUNCTIONAL CONDITION OF HEART - S. E. Qasimov (Евразийский Кардиологический Журнал)
The purpose of this study was a comparative assessment of pathological changes in the morpho-functional condition of the heart in groups of patients with arterial hypertension, divided by salt sensitivity.Material and methods. 93 patients with arterial hypertension (AH) and concomitant coronary heart disease were included in the study. All patients were subjected to a salt load, after which all patients were divided into groups of salt-sensitive (SS) and nonsalt-sensitive (NSS) patients. Along with this, the patient was replicated with an echocardiographic examination of the heart to determine the functional state of the heart muscle. Patients in the SS and NSS groups were compared by heart echocardiography results.Results. Left ventricular hypertrophy was found to be more prevalent in the group of SS patients compared to the NSS group (82.6% vs. 17.0%) and the differences between the groups were statistically significant (p<0.001). In many cases, some echocardiographic parameters, such as left ventricular posterior wall thickness and intra-ventricular thickness, were higher in patients with SS, which indicated significant early remodeling of the heart in these patients.Conclusions. The obtained data allow us to judge about the more pronounced and early occurrence of myocardial hypertrophy in SS patients.